Speech Acts, Directness and Politeness in Dubbing: American Television Series in Hungary: (Oxford: Peter Lang, 2020. New Trends in Translation Studies vol. 30. 254 pp. ISBN 978-1-78874-232-0) - Malaczkov, Szilvia (Fordítástudomány, 2020)
Polcz Károly Speech Acts, Directness and Politeness in Dubbing: American Television Series in Hungary (Oxford: Peter Lang, 2020. New Trends in Translation Studies vol. 30. 254 pp. ISBN 978-1-78874-232-0)